Implementasi Alat Musik Tradisional Songah di Era Globalisasi Pada Anak Sekolah Dasar - Rizma Rubia Ningsih; Dinie Anggraeni Dewi; Rizky Saeful Hayat (PT. ALHAFI BERKAH INDONESIA, 2023)
People in the current era of globalization tend to prefer new cultures which are considered more practical compared to local culture. This of course has an impact on the fading of local culture, as a result of the lack of future generations who have an interest in learning and preserving it. This research specifically aims to describe the implementation of the traditional Songah musical instrument, a traditional musical instrument typical of the Sumedang region, West Java in the midst of globalization. The research method used in this research is a qualitative descriptive method. The research was carried out in an elementary school in one of the districts in West Java Province with data collection techniques used, namely observation, interviews and documentation. The research subjects are students, teachers and pupils who are important components in the research. The results obtained are that this implementation has quite an impact on students, apart from being enthusiastic about participating in activities, it can also foster a sense of nationalism and love for the country. Therefore, Songah musical instruments can be applied in implementing local wisdom-based learning, in order to create the next generation as heirs to local culture which is starting to be eroded by the flow of globalization.